Pulmonary hamartoma mimicking lung tuberculoma in tuberculosis patient – a case report - Krawczyk, Paweł; Wojas-Krawczyk, Kamila; Czekajska-Chehab, Elżbieta; Kieszko, Robert; Zdunek, Małgorzata; Sawicki, Marek; Milanowski, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Pulmonary hamartomas are benign tumors, which represent abnormal mixture of fibrous connective tissue, hyaline cartilage, fat and bone as well as bronchial epithelial cells. Differential diagnosis of tuberculoma, malignant neoplasms and hamartoma is necessary. We present the tuberculosis patient with pulmonary hamartoma mimicking lung tuberculoma. The uncorrected diagnosis of tuberculoma was made based on symptoms and CT imaging. However, histopathologic analysis of surgically enucleated tumor confirmed non-infectious origin of the lesion (hamartoma with hyaline cartilage predominance).